Interplay between hydrodynamics and jets - Zapp, Korinna Christine; Flörchinger, Stefan (Nuclear physics. A, Nuclear and hadronic physics, 2014)
By combining the jet quenching Monte Carlo Jewel with a realistic hydrodynamic model for the background we investigate the sensitivity of jet observables to details of the medium model and quantify the influence of the energy and momentum lost by jets on the background evolution. On the level of event averaged source terms the effects are small and are caused mainly by the momentum transfer.